Reinforcing knowledge and business relationships among associated bean producers in Honduras - Reyes, Byron A.; Espada, Andrés; Ceballos Sierra, Federico; Colindres, Mirian; Wiegel, Jenny (2023)
The Rethinking Food Markets and Value Chains for Inclusion and Sustainability Initiative aims to provide evidence on what types of bundled innovations, incentive structures, and policies are most effective at creating more equitable sharing of income and employment opportunities in growing food markets, while reducing the food sector’s environmental footprint. Its work is organized in four working groups (Work Packages-WP). One of these groups focuses on food value chains serving domestic markets. Within its scope of research, the mentioned WP concentrates on identifying opportunities to improve participation and profit of smallholder farmers and agrifood small and medium enterprises (SMEs), and lowering their environmental footprint by identifying, adapting, and scaling interventions. For this, it is evaluating the effectiveness and synergies between innovations in the domestic chain of common beans in Honduras. This WP is implementing a pilot evaluation together with two farmer associations, to test the effectiveness of three innovations, using a randomized controlled trial. This report summarizes the results of the farmer-level baseline survey, implemented in late 2023, in the context of this evaluation.